1985
DOI: 10.3109/00016348509154707
|View full text |Cite
|
Sign up to set email alerts
|

Suprapubic Versus Transurethral Bladder Drainage After Colposuspension/Vaginal Repair

Abstract: Ninety-two patients with preoperative sterile urine undergoing colposuspension or vaginal repair operation for stress urinary incontinence and/or genital descensus were randomized to either suprapubic or transurethral postoperative catheter drainage. The prevalence of significant bacteriuria on the fifth postoperative day was statistically significantly lower when using suprapubic catheter (20.8%) than with transurethral catheter drainage (45.5%). This applied especially to colposuspension. The rate of postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 5 publications
1
41
0
1
Order By: Relevance
“…The limited data available suggest that suprapubic catheters, external catheters (in men), and intermittent catheterization may be associated with lower rates of bacteriuria, UTI, or both than intra-urethral catheters. 52,[66][67][68][69] Of course, in both geriatric patients and individuals with SCI, the patient's functional status often influences the type of bladder management, so randomized comparisons of these various drainage methods are not possible. 50,70,71 Strategies effective only for short-term catheterization Although changing catheter materials to render the catheter surface inhospitable to biofilm formation is a clever idea, this approach is effective for prevention of UTI only in the setting of short-term catheterization.…”
Section: Possibly Effective Strategiesmentioning
confidence: 99%
“…The limited data available suggest that suprapubic catheters, external catheters (in men), and intermittent catheterization may be associated with lower rates of bacteriuria, UTI, or both than intra-urethral catheters. 52,[66][67][68][69] Of course, in both geriatric patients and individuals with SCI, the patient's functional status often influences the type of bladder management, so randomized comparisons of these various drainage methods are not possible. 50,70,71 Strategies effective only for short-term catheterization Although changing catheter materials to render the catheter surface inhospitable to biofilm formation is a clever idea, this approach is effective for prevention of UTI only in the setting of short-term catheterization.…”
Section: Possibly Effective Strategiesmentioning
confidence: 99%
“…It is reported that in patients undergoing abdominal, gynecological or vascular surgery, postoperative discomfort was significantly higher in patients with urethral versus suprapubic catheterization. [5][6][7] Although many studies have recently shown that cystography can direct early catheter removal with no increase in morbidity, 8,9 and there has been a movement towards shortened catheterization, 10,11 the optimal timing for catheter removal is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with urethral catheterisation, SPC is associated with a superior quality of life, reduced infection rates and less pain and discomfort. It also enables patients, especially males to attempt normal voiding [2][3][4][5]. There is evidence to suggest that SPC are more acceptable to patients [3,4,6], with one study suggesting that 89% prefer SPC to urethral catheters [1].…”
Section: Introductionmentioning
confidence: 99%